Reduction and temperature-responsive hydrogel composed of hydroxyethyl disulfide-bis-glycidyl ether-crosslinked poly(hydroxyethyl acrylate-co-methyl methacrylate). Issue 8 (24th May 2022) - Yoon, Dong Youl; Alle, Madhusudhan; Kim, Jin-Chul
Abstract: Reduction and temperature-responsive gels were prepared by crosslinking poly(hydroxyethyl acrylate- co -methyl methacrylate) (poly(HEA- co -MMA)) using hydroxyethyl disulfide-bis-glycidyl ether(HEDSGE) as a disulfide cross-linker. Poly(HEA- co -MMA) exhibited lower critical solution temperature (LCST) behavior when MMA content was 7.4 and 8.3 mole %. Energy dispersive X-ray and Raman spectroscopy revealed that the copolymer chains of the gels were cross-linked by disulfide bond (i.e., HEDSGE). The gels released their content in proportion to the concentration of a reducing agent (i.e., dithiothreitol). In addition, the gels released their payloads in a temperature dependent manner, possibly due to the LCST property of the copolymer. Highlights: Reduction and thermo-responsive gels were prepared by crosslinking poly(HEA-co-MMA) using HEDSGE. Poly(HEA- co -MMA) exhibited LCST behavior when MMA content was 7.4 mole % and 8.3 mole %. Gels released their content in proportion to dithiothreitol (a reducing agent) concentration. Gels released their payloads in a temperature dependent manner. Graphical Abstract: UF0001